2021
DOI: 10.1002/adfm.202009489
|View full text |Cite
|
Sign up to set email alerts
|

Delivery Techniques for Enhancing CAR T Cell Therapy against Solid Tumors

Abstract: Chimeric antigen receptor (CAR) T cells exhibit promising results for cancer immunotherapy. However, the clinical success is still restricted to certain types of blood cancers, while in solid tumors the clinical activity is modest and potential toxicities remain a concern. There are various barriers that prevent CAR T cells from combating solid tumors. Therefore, distinct strategies have been explored to augment CAR T cell proliferative capacity, persistence, and effector function. Altering the tumor microenvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 109 publications
(127 reference statements)
0
21
1
Order By: Relevance
“…[14,15] Despite circumventing intratumoral IB, the dominantly-used local delivery of CAR-T cells by using hydrogel as a reservoir is incapable of adequately activating systematic immune responses, [20] thereby leading to failure in treating multiple nodules and metastasized ones. [21][22][23] Additionally, genetically engineering T cells with new CARs remains ineffective for addressing different concerns (i.e., insuffi-cient CAR-T in vivo) since the re-injected CAR-T cells fail to continually expand, thus highlighting the non-persistence of CAR-T immunotherapy for solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] Despite circumventing intratumoral IB, the dominantly-used local delivery of CAR-T cells by using hydrogel as a reservoir is incapable of adequately activating systematic immune responses, [20] thereby leading to failure in treating multiple nodules and metastasized ones. [21][22][23] Additionally, genetically engineering T cells with new CARs remains ineffective for addressing different concerns (i.e., insuffi-cient CAR-T in vivo) since the re-injected CAR-T cells fail to continually expand, thus highlighting the non-persistence of CAR-T immunotherapy for solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The remote manipulation of ligand coupling shown in this study has not been reported in previous studies that modulated only linearly shaped ligands in diverse nano-sequences [48] or nano-patterns, [49] and dynamically modulated only the activation of planarly distributed ligands via UV light, [34] or only the stretching of linearly shaped nano-coiled ligands via a magnetic field. [55] Our materials presenting movably couplable ligands offer the tunability of dimensions, [66][67][68][69] alignment, and bioactive ligands of the MLNs and the dimensions of the AuNPs, [70] which can provide fundamental insight to elucidate the dynamic interplay between ligand coupling and integrin recruitment that modulates stem cell adhesion, mechanosensing, and differentiation.…”
Section: Dynamic Ligand Coupling Regulates Focal Adhesion Mechanosens...mentioning
confidence: 99%
“…The reasons for the slow advancement in CAR-T cells for the treatment of HNSCC are associated with the barriers formed by the unique tumor microenvironment (TME) of solid tumors, and are as follows: (1) physical barriers, including compact tumor structures, tumor stromal cells, etc., (2) physiochemical barriers, including the downregulation of cytokines and acidic, hypoxia and low-nutrient environments and (3) pathological barriers, including immunosuppressive mechanisms, immune checkpoints, tumor antigen loss and heterogeneity, etc. These barriers restrict the infiltration of CAR-T cells into HNSCC, influence the specificity of HNSCC cell targeting and decrease the proliferation and anti-tumor effect of CAR-T cells [ 62 , 63 , 64 ]. Strategies to overcome these three barriers in solid tumors are regarded as the key point of accelerating the clinical translation of CAR-T cell therapy.…”
Section: Barriers Of Car-t Cell Therapy In Hnscc and Potential Solutionsmentioning
confidence: 99%